Prevalence and Associated Factors of Pressure Ulcer among Hospitalized Patients at Felegehiwot Referral Hospital, Bahir Dar, Ethiopia. (16th December 2014) - Gedamu, Haileyesus; Hailu, Mignote; Amano, Abdella
Abstract : Introduction . Pressure ulcers, also known as decubitus ulcers (bed sores), are localized skin injuries that remain a major health problem affecting approximately 3 million adults. Objective . The aim of this study was to assess the prevalence and associated factors of pressure ulcer among hospitalized patients in Felegehiwot referral hospital. Methods . This cross-sectional study used systematic sampling on a sample of 422 patients. The data was collected by trained data collectors through pretested checklist. Bivariate analysis was used principally and variables were then entered into multiple logistic regressions model for controlling the possible effect of confounders and the variables which have significant association were identified on the basis of OR with 95% CI and P value. Results . The finding of this study revealed that 71 (16.8%) of them had pressure ulcer. Prolonged length of stay in hospital, slight limit of sensory perception, and friction and shearing forces were significantly associated with the presence of pressure ulcer. Conclusions and Recommendations . The prevalence of pressure ulcer was high among hospitalized patients. Researches of prospective (follow-up) study required investigating the incidence and associated factors of pressure ulcer for hospitalized patients.